2003
DOI: 10.1007/s00018-003-3110-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neutrophil apoptosis via death receptors

Abstract: Human neutrophils constitutively undergo apoptosis, process which is critical for the successful resolution of inflammation by the safe removal of effete cells. A wide variety of agents can modulate neutrophil apoptosis and these act through multiple and complex receptor-signalling pathways. Whilst these pathways can be initiated via distinct cell surface receptors, many downstream intracellular pathways can converge, use common molecules or trigger similar cellular activities, such as activation of caspases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 48 publications
3
62
0
Order By: Relevance
“…This may in turn trigger the activation of NF-B and activator protein 1, which may induce the expression of survival factors, thus providing resistance against apoptosis. The response of the neutrophil to TNF␣ is very much concentrationdependent (35,36). In our present study, TNF␣ levels were observed to be low in juvenile-onset SLE sera compared with control sera.…”
Section: Role Of Neutrophil Apoptosis In Juvenile-onset Sle 2397supporting
confidence: 49%
See 1 more Smart Citation
“…This may in turn trigger the activation of NF-B and activator protein 1, which may induce the expression of survival factors, thus providing resistance against apoptosis. The response of the neutrophil to TNF␣ is very much concentrationdependent (35,36). In our present study, TNF␣ levels were observed to be low in juvenile-onset SLE sera compared with control sera.…”
Section: Role Of Neutrophil Apoptosis In Juvenile-onset Sle 2397supporting
confidence: 49%
“…It is therefore unlikely that a single factor in juvenile-onset SLE sera is responsible for the enhanced neutrophil apoptosis, but rather, that a combination of these factors leads to enhanced cell death. Exposure of cells to TNF␣ can induce multiple effects, including cell differentiation, proliferation, apoptosis, and other proinflammatory effects (35). TNF␣ can induce apoptosis through TNF receptor I in some cell types, including neutrophils.…”
Section: Role Of Neutrophil Apoptosis In Juvenile-onset Sle 2397mentioning
confidence: 99%
“…Fas is a quintessential death receptor in neutrophils (28,29), and it is known to stimulate ectodomain shedding (12)(13)(14). Because Fas-mediated signaling events do not always involve caspases (30,31), we initially examined their requirement in ADAM17 stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to other proinflammatory mediators, TNFa is a unique cytokine which possesses both proapoptotic and antiapoptotic activity, depending on the intracellular and extracellular environment [108]. Survival is usually induced at low doses of TNFa, while proapoptotic effects were observed at high doses [109].…”
Section: Tnfamentioning
confidence: 99%